EXPERTS COUNCIL RESOLUTION/ CLINICAL SIGNS, MANAGEMENT AND MONITORING ALGORITHMS OF PATIENTS WITH MPS I WHO HAVE UNDERGONE HEMATOPOIETIC STEM CELL TRANSPLANTATION. THE ROLE OF ERT IN MPS I MANAGEMENT AFTER HSCT - article Editorial (Вопросы современной педиатрии)
.